Primary neuroendocrine carcinomas of the breast and neuroendocrine differentiated breast cancers: Relationship between histopathological and radiological features. Issue 147 (February 2022) - Kayadibi, Yasemin; Erginoz, Ergin; Cavus, Gokce Hande; Kurt, Seda Aladag; Ozturk, Tulin; Velidedeoglu, Mehmet
Highlights: Neuroendocrine tumors of breast are usually seen as irregularly shaped masses with circumscribed or microlobulated margins and without microcalcifications. On ultrasonography, they are usually located parallel to the skin and do not give a posterior acoustic shadow. Although neuroendocrine tumors of breast can be observed most frequently as a mass lesion, they can also present as a non-mass lesion. Although neuroendocrine tumors of the breast are hormone receptor positive, they can mimic hormone receptor negative tumors in terms of their imaging findings. Abstract: Purpose: The aim of this study was to investigate whole-breast imaging findings (mammography, ultrasonography (US), magnetic resonance imaging (MRI),  clinical, and histopathological findings of primary neuroendocrine carcinomas of the breast (NEC) and neuroendocrine differentiated breast cancers (NEBC). Methods: Patients with a diagnosis of breast cancer with histopathological neuroendocrine features between the years 2010 and 2021 were retrospectively screened. The lesions were divided into two main groups depending on staining with neuroendocrine markers (synaptophysin and chromogranin A). Those showing focal staining were categorized as NEBC while those with diffuse staining as NEC. The mammography, US, and MRI of the lesions were reviewed in consensus by two breast radiologists in order to assess imaging features retrospectively according to the Breast Imaging Reporting and Data System (BI-RADS) 5th lexicon. The findings were compared with breast cancers without neuroendocrine features (BC-WNE) which were randomly selected from the same database. Results: A total of 105 lesions [NEBC (n = 44), NEC(n = 11), BC-WNE (n = 50)] were evaluated. Patients with neuroendocrine tumors were older (p < 0.001) than those with BC-WNE. Compared with BC-WNE tumors, radiological findings typical of malignancy such as irregular shape [NEBC (7/20); NEC(3/7) vs BC-WNE (35/43); p < 0.001], spiculation [NEBC (2/20); NEC(0/7) vs BC-WNE (21/43); p < 0.001], architectural distortion [(NEBC (3/24); NEC(0/9) vs BC-WNE (31/50); p < 0.001)], calcification [(NEBC (6/24), NEC(0/9) vs BC-WNE (n = 27/50); p = 0.001)] on mamography, non-parallel orientation to skin [(NEBC (n = 17/29), NEC(n = 4/9), BC-WNE (n = 35/42); p = 0.008)], acoustic shadowing [(NEBC (n = 12/29), NEC(1/9), BC-WNE (n = 29/42); p = 0.009)], axillary lymphadenopathy [(NEBC(n = 3/30), NEC(n = 1/9), BC-WNE (21/50); p < 0.001)]on US were less common features of the neuroendocrine carcinomas of breast. Aside from shape features, there was no significant difference in contrast pattern (p = 0.866), kinetic curve (p = 0.454) and diffusion restriction (p = 0.242) on MRI. Conclusion: Characteristic malignant imaging features, including irregular shape, spiculated margins, suspicious calcifications, and posterior acoustic shadowing, are uncommon in neuroendocrine carcinomas of breast. These carcinomas tend to show more benign imaging features when compared with BC-WNE.